Analysis of Instrumentation Application in the Implementation of Evaluation of Guidance and Counseling Services in SMP Pekanbaru City - Raja Rahima Munawarah Raja Ahmad; Hasgimianti; Ku Hidayatullah Binti Ku Ismail; Nurhafiza (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
The implementation of evaluating counseling service activities must be based on accurate and accountable data, utilizing the appropriate instrumentation application. The purpose of this study was to describe the use and obstacles of instrumentation applications in evaluating counseling services. This research is a descriptive qualitative field research survey method. The sample schools were 10 junior high schools in Pekanbaru City. The research data was taken using a structured interview method, and processed using the Miles & Huberman approach with steps 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusion drawing. The findings in this study are as follows: 1) The evaluation instruments used by counseling teachers include questionnaires, observations, LKPD, IKMS, Psychological Tests, Case Studies, and DCM. 2) The constraints of counseling teachers in using counseling instrumentation internally include the skills of counseling teachers in using counseling instruments, a lack of interest in attending training on counseling instrumentation, and externally related issues such as counseling programs that have not been implemented, as well as the absence of counseling instrumentation available at school. The implications of this research will encourage counseling teachers to use instrumentation in counseling services. Keywords: instrument application, evaluation implementation, guidance and counseling services